Serving the Church and the Nation: Gratefully and Faithfully - Kuruvilla Pandikattu and others; PANDIKATTU (Kuruvilla) Ed; VAZHAPILLY (Sebastian) Ed; LANKAPALLI (Prasad) Ed (Pune Jnana Deepa Vidyapeeth, 2020)
How can we serve the Church and Nation creatively and meaningfully? Papal Seminary in India was established in 1893 to enable the Christians and Indians to lead lives that are grateful, faithful and so joyful. To celebrate 125 years of Papal Seminary, a seminar was held to reflect on the challenges that the present church in India faces, as well as the opportunities offered to her. So the 28 articles in this book offer relevant reflections on how we can be meaningfully committed to India by serving its people in the spirit of Christian values and vision. The book seeks to promote a Gospel values of respect, compassion, hope and joy in the people.
Keywords: India; Mysticism--Christianity; Christian life; Church; Church and social problems; Church work